SOFTWARE «PRONEUROLIT» FOR PROTOTYPING OF FOUNDRY TECHNOLOGIES - A. N. Chichko; Ju. V. Jatskevich; V. F. Sobolev; T. V. Matushinets; O. I. Chichko (Литьë и металлургия, 2010)
The neuronet algorithm and software «ProNeuroLit» are developed for choice of prototypes of gating systems on the basis of database of analogues. The different regimes of operation of «proneurolit» by choice of gating systems are shown.